Comparison of isokinetic muscular strength of knee according to female volleyball and table tennis players - Park, S.-E.; Kim, Y.-Y.; Park, S.-J. (Journal of Convergence for Information Technology, 2019)
The purpose of this study was to compare the isokinetic muscular strength of the knee joint between female volleyball and table tennis players. A total of 27 elite volleyball players and 27 table tennis players participated in the study. This study measured both knee extensor and flexor strengths of volleyball and table tennis players using the isokinetic dynamic test. Peak torque was measured by performing maximal voluntary flexion and extension three times at 60°/s. Volleyball players had higher knee extensor and flexor strengths than table tennis players. No significant difference in both knee strengths was noted in table tennis players. However, volleyball players showed significant differences in both knee strengths. Height and weight showed a positive correlation with knee strength. This study found that volleyball players had greater knee strength than that of table tennis players. We also found that volleyball players have asymmetrical knee strength. Comparison with other sport players is warranted to better understand isokinetic muscular strength of the knee joint.